PENGARUH SOSIAL EKONOMI, SARANA DAN PRASARANA TERHADAP PERILAKU MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KECAMATAN AMPANA KOTA KABUPATEN TOJO UNA-UNA - Hardi, Hijrah (Katalogis, 2017)
The study intends to know: 1) significant influence of social economy and infrastructure simultaneously towards community behavior on waste management in Ampana Sub-District in Tojo Una-Una; 2) significant influence of social economy towards community behavior on waste Mmanagement in Ampana Sub-District in Tojo Una-Una; 3) significant influence of infrastructure towards community behavior on waste management in Ampana Sub-District in Tojo Una-Una. Sample consists of 99 respondents from 6 urban villages and 4 villages in Ampana City Sub-District. Data analyzed with descriptive quantitative approach with multiple linear regressions analysis. The result shows that social economy and infrastructure simultaneously and partially have significant influence towards community behavior on waste management in Ampana Sub-District in Tojo Una-Una.